Zero Tolerance and Other Plays - Goldstein, Tara. author. aut Link
Approx. 5 p.
Keywords: A wealth of evidence demonstrates that disabled domestic students experience disabling barriers in such areas as funding, pedagogy and social life in Higher Education (HE). Research also indicates that non-disabled international students experience a wide range of cultural and linguistic difficulties throughout their university experience whilst studying in England. Nevertheless, there is a dearth of research concerning the specific experiences of disabled international students in English universities. With the increasing internationalisation of HE in the past two decades this is highly significant. Analysing disabled international students’ accounts in British universities appears to be all the more pertinent due to the current austerity measures, which have impacted on the financial situation of Higher Education Institutions. Armineh Soorenian comments on the relevance of inclusive educational theories and policies within an increasingly internationalised HE system, with reference to disabled international students’ experiences in England. The project is both timely and appropriate as there is an acute shortage of documentation on the application of policies for the inclusion of disabled students and disabled international students specifically in English universities. The findings identify key barriers in the four broad categories of (1) Information, Access and Funding; (2) Disability Services; (3) Learning and Teaching; and (4) Non-Disability Support Services such as accommodation and social life. The study provides an up-to-date snapshot of disabled international students’ accounts and the multiple disadvantages they experience in their universities based on their identities as ‘disabled’, ‘international’ and sometimes ‘mature’ students. The author also draws on a number of insights which could contribute towards a more inclusive HE system. The implication of concentrating on disabled international students’ experiences have directramifications, not only for this specific group, but also a wide range of students from diverse minority backgrounds who could gain from inclusive practices in education.